2017
DOI: 10.1177/1534735416681639
|View full text |Cite
|
Sign up to set email alerts
|

Potential Contributions of Antioxidants to Cancer Therapy: Immunomodulation and Radiosensitization

Abstract: Antioxidants play important roles in the maintenance of cellular integrity and thus are critical in maintaining the homeostasis of the host immune system. A balance between the levels of pro-oxidants and antioxidants defines the cellular fate of genomic integrity via maintaining the redox status of the cells. An aberration in this balance modulates host immunity that affects normal cellular signaling pathways resulting in uncontrolled proliferation of cells leading to neocarcinogenesis. For decades, there have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(76 citation statements)
references
References 87 publications
1
74
0
1
Order By: Relevance
“…Recently, the intake of antioxidants has been considered as a possible strategy to improve overall health (24,25). Antioxidants play important roles in redox signaling and redox status of cells and thereby the maintenance of cellular integrity and homeostasis (26). Also, several clinical trials have suggested that antioxidants benefit cancer therapy (27).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the intake of antioxidants has been considered as a possible strategy to improve overall health (24,25). Antioxidants play important roles in redox signaling and redox status of cells and thereby the maintenance of cellular integrity and homeostasis (26). Also, several clinical trials have suggested that antioxidants benefit cancer therapy (27).…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidants are known to mediate the key activities of cellular integrity maintenance and thus maintains the homeostasis of the host immune system. The genomic integrity of a cell is determined by the balance of pro-oxidants and the levels of antioxidants and an aberration in this balance can alter the normal cellular signaling cascades (Thyagarajan et al, 2018). Further, the alterations in the cellular signaling pathway can initiate the process of neocarcinogenesis (Monisha et al, 2017;Roy et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of GSH synthesis by a specific glutaminase (GLS) inhibitor and the simultaneous treatment with hydrogen peroxide resulted in a high apoptosis rate in ccRCC (58). Hence, additional administrationof antioxidants during (chemotherapeutic) cancer treatment have been frequently shown to have no or even pro-tumor effects (59,60). High GSH levels in RCC, which protect the tumor from increased ROS stress, should therefore be therapeutically exploited by reducing the antioxidant levels, of GSH, and increasing ROS stress at the same time to a level where healthy cells can still survive, but tumorous cells are forced into apoptosis.…”
Section: Discussionmentioning
confidence: 99%